Gradual chromosomal lagging drive programmed genome elimination in hemiclonal fishes from the genus Hypseleotris - Dedukh, Dmitrij; Majtánová, Zuzana; Ráb, Petr; Ezaz, Tariq; Unmack, Peter J (Scientific reports, 2024)
Most eukaryotes maintain the stability of their cellular genome sizes to ensure genome transmission to offspring through sexual reproduction. However, some alter their genome size by selectively eliminating parts or increasing ploidy at specific developmental stages. This phenomenon of genome elimination or whole genome duplication occurs in animal hybrids reproducing asexually. Such genome alterations occur during gonocyte development ensuring successful reproduction of these hybrids. Although multiple examples of genome alterations are known, the underlying molecular and cellular processes involved in selective genome elimination and duplication remain largely unknown. Here, we uncovered the process of selective genome elimination and genome endoreplication in hemiclonal fish hybrids from the genus Hypseleotris. Specifically, we examined parental sexual species H. bucephala and hybrid H. bucephala × H. gymnocephala (HB × HX). We observed micronuclei in the cytoplasm of gonial cells in the gonads of hybrids, but not in the parental sexual species. We also observed misaligned chromosomes during mitosis which were unable to attach to the spindle. Moreover, we found that misaligned chromosomes lag during anaphase and subsequently enclose in the micronuclei. Using whole mount immunofluorescent staining, we showed that chromatid segregation has failed in lagging chromosomes. We also performed three-dimensional comparative genomic hybridization (3D-CGH) using species-specific probes to determine the role of micronuclei in selective genome elimination. We repeatedly observed that misaligned chromosomes of the H. bucephala genome were preferentially enclosed in micronuclei of hybrids. In addition, we detected mitotic cells without a mitotic spindle as a potential cause of genome duplication. We conclude that selective genome elimination in the gonads of hybrids occurs through gradual elimination of individual chromosomes of one parental genome. Such chromosomes, unable to attach to the spindle, lag and become enclosed in micronuclei.
Keywords: Genome Size; Male; délka genomu; Histone modification; chromozomy; Gonads; Mitosis; Gonocytes; mužské pohlaví; ryby; Asexual; Fishes; genom; segregace chromozomů; Animals; ženské pohlaví; Chromosomes; zvířata; Carp gudgeon; Hybridization, Genetic; Hybridogenesis; hybridizace genetická; mitóza; Genome; Chromosome Segregation; Female; Micronucleus; gonády